2013
DOI: 10.1111/febs.12460
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the biochemical function of Agrobacterium T‐complex‐recruiting protein Atu5117

Abstract: Atu5117 from Agrobacterium tumefaciens is a highly conserved protein with a putative nucleotidyltransferase domain in its N-terminal region and a putative higher eukaryotes and prokaryotes nucleotide-binding domain in its C-terminal region. This protein has been shown to be a T-complex-recruiting protein that can recruit T-complex from the cytosol to the polar VirB/D4 type IV secretion system (T4SS). However, the biochemical function of Atu5117 is still unknown. Here, we show that Atu5117 is a (d)NTPase. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Associated functional studies of the HEPN domain of VBP have demonstrated that the dimerization of VBP is essential for the induction of tumors in plants ( Padavannil et al, 2014 ). Our recent experimental data confirmed that VBP1 (encoded by atu5117 ) is an NTPase that might energize the recruitment of T-complex to the transport site ( Gao et al, 2013 ).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Associated functional studies of the HEPN domain of VBP have demonstrated that the dimerization of VBP is essential for the induction of tumors in plants ( Padavannil et al, 2014 ). Our recent experimental data confirmed that VBP1 (encoded by atu5117 ) is an NTPase that might energize the recruitment of T-complex to the transport site ( Gao et al, 2013 ).…”
Section: Introductionsupporting
confidence: 58%
“…Bioinformatics investigations have demonstrated that three VBPs are highly conversed with regard to their functional domains, and all of the VBPs contain a putative nucleotidyltransferase domain near the N-terminus and a putative higher eukaryotes and prokaryotes nucleotide-binding (HEPN) domain near the C-terminus ( Guo et al, 2007b ; Gao et al, 2013 ). Structural studies have shown that VBP is a dimer and that the C-terminal HEPN domain is the dimerization domain of VBP.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophoresis and immunoblotting analyses were carried out as described before [ 27 , 40 ]. Equal volumes (10 μL) of various samples were loaded for SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%